Corn yield as affected by row pattern, plant density, and irrigation system. Issue 4 (4th July 2022) - Sorensen, Ronald B.; Lamb, Marshall C.; Butts, Christopher L.
ABSTRACT: Row crops normally grown in Southeast USA are cotton ( Gossypium hirsutum L.), corn ( Zea mays L.), and peanut ( Arachis hypogea L.) with a focus on the higher economic value for peanut. Peanut is typically planted using a twin-row pattern and purchasing a twin-row planter may not be cost effective unless used with other rotational crops. The objectives were to compare corn yield when planted in twin-rows, with two plant densities, at multiple locations, and irrigated with drip or sprinkler system. Corn was planted in single and twin-row patterns at 7.9 seeds/m (normal; 86, 100 seeds/ha) and 4.9 seeds/m (half-normal; 53, 600 seeds/ha) at multiple locations and cropping seasons. Irrigation systems consisted of subsurface drip (SSDI), shallow subsurface drip (S3DI) and overhead sprinkler. Single and twin-row with normal seeding rate had same yield across years, locations, or irrigation system 88% of the time. With drip irrigation only, twin-row half-normal seeding rate had the same yield as the single-row normal seeding rate 75% of the time and when factoring in seed savings had an economic benefit of $56/ha. The single-row half-normal seeding rate always had lower yield compared with other treatments. The S3DI irrigation system had greater yield than SSDI for both row patterns and seeding rates. Therefore, a twin-row planter purchased for peanut may be used to plant corn without yield reduction using normal seeding rates under either drip or sprinkler irrigation systems.